Low Prevalence of Antibodies Against Toxoplasma gondii in Chinese Populations - Xin, Shilin; Su, Ruijing; Jiang, Nan; Zhang, Longxian; Yang, Yurong (Frontiers in Cellular and Infection Microbiology, 2020)
Toxoplasma gondii has been found to infect almost all warm-blooded animals, including humans. In this study, a total of 3,275 human serum samples were collected from hospitals in five provinces of China. About 5.13% (168/3,275) (95% CI, 4.42–5.94) of the serum samples were positive for T. gondii IgG antibody by a modified agglutination test (MAT) (cut-off: 1: 20). Significant associations were detected between geographic location (OR=1.763), age (OR=3.072), infertile in women (OR=2.4409) and T. gondii infection in humans (p < 0.05). To minimize infection, citizens need to be informed about the risk factors of toxoplasmosis, including eating well-cooked meat, drinking boiled water, washing vegetables and fruits, and being careful when contacting with cats.